Analisis Building Information Modelling (BIM) 5D Pada Pekerjaan Struktur Beton Bertulang Bangunan Kantor Kebun Muara Lawa - Setiawan, Ikbal; Hendriyani, Irna; Pratiwi, Reno (Indonesian Society of Applied Science, 2025)
In this modern era, the construction industry has undergone a significant transformation with the adoption of digital technology. One of the innovations in the construction industry today is Building Information Modeling, or BIM, as a tool to manage projects efficiently and become part of the digital industrial sector. Accuracy in construction cost estimation is very important to get an efficient value in planning. Currently, cost budget calculations on development projects still often use conventional methods that produce greater value. Therefore, this research uses the concept of BIM dimension 5D which aims to analyze the volume and cost estimates and analyze the difference in volume and cost using the BIM dimension 5D method and conventional methods on the construction of the Muara Lawa West Kutai Garden Office Development structure. The results of the research on the structural work of the Muara Lawa Kutai Barat Office Garden Development using the 5D concept produced a steel volume of 1102.14 kg with a cost of Rp. 18,956,808.00. A concrete volume of 6.6 m3 with a cost of Rp. 30,201,875. This resulted in a steel volume difference of 13.53% and a concrete volume difference of 10.22%. This means that the calculations using the 5D BIM concept are lower compared to the cost planning produced by the Contractor.